The Different Capability Of Metal Uptake In The Shell Of Perna Viridis Compared To The Different Soft Tissues: A Statistical Approach - Yap, Chee Kong; Edward Thomas, Franklin Berandah (Universiti Malaysia Terengganu, 2009)
Distribution of metals in bivalves is usually examined based on different metal concentrations in the different tissues of the bivalves. Patterns of metal distribution between the shells and the different soft tissues of two geographical populations of the green-lipped mussel Perna viridis were investigated. The correlation analysis showed insignificant correlation between the shells and the different soft tissues. The multiple linear stepwise regression analysis showed that the shells were not influential in metal accumulation in the total soft tissues. The cluster analysis showed that the shells were clustered differently, as a single entity, from the rest of the different soft tissues. All these findings indicate that the capability of metal uptake by the shell of Perna viridis differs.